Birokrasi Pemerintahan Dalam Perspektif Ekonomi Islam - Agung Eko Purwana (Justicia Islamica, 2011)
In economic activities, the government has a very important role in allocating and distributing economic resources for the greatest prosperity of its people. In addition, the government also has a role as a tool for economic stabilization. But, these roles of government is not functionless properly. One of the reasons is the corrupt practices of bureaucracy.The scholars do a lot of studies about how to make the bureaucracy work unimpeded by corrupt practices. The same study is done by Muslim scholars and economists. They offer new alternatives based on Islamic law and Shari’ah. Shari’ah demanded to its adherents to act professionally in the process displaying neatness, correctness, order, and regularity. From this point of view, the paper would examine how Islamic economic perspective has a study on the duties of a government, especially in carrying out its functions, namely: allocation, distribution, and stabilization.